Alpha defensin expression in white blood cells - Allen, Naomi (2019)
Copy number variation (CNV) accounts for a large proportion of genetic variation. The DEFA1A3 CNV has variable numbers of copies of the DEFA1 and DEFA3 genes that encode alpha defensins 1-3, antimicrobial peptides abundant in human neutrophils. Association studies have found associations between this locus and autoimmune diseases such as IgA nephropathy and periodontitis, though the disease mechanisms by which this association occurs are not yet fully understood. Previous investigations into the locus have found inconsistent results for expression of alpha defensin in subsets of white blood cells other than neutrophils. The objective of this project was to investigate the expression of alpha defensins in white blood cells and to determine if expression was variable based on genotype.